Integration of Faith and Piety with IPTEK of Islamic Education According to Bj Habibie - Muthoharoh, Imroatul; Fahmi, Alif Anharul; Ramadhan, Muhammad Fadli (Al-Liqo: Jurnal Pendidikan Islam, 2024)
This study aims to find out the concept of integration of imtaq and science and technology according to BJ. Habibie. The method used is the character study methodology with library research. The primary data source comes from books written by BJ Habibie as well as documentation in the form of his video shows. Meanwhile, secondary data sources come from books that are related to the research topic. The results of this study:  His concepts and ideas regarding the need for integration between imtaq and science and technology in Islamic educational institutions to answer the backwardness of Muslims in the fields of science and technology, but still have a strong foundation of faith and piety. According to Habibie imtaq is a positive synergy of cultural elements and religious elements from the acculturation process in the family. While science and technology are the result of the educational process that is pursued by humans. The educational process that combines imtaq and science and technology will give birth to humans who are able to think analytically, systematically, deeply and long term. The result will be born science. Science will give birth to technology. These two dimensions must be synergized to form a superior human being.